1999
DOI: 10.3171/jns.1999.91.4.0669
|View full text |Cite
|
Sign up to set email alerts
|

Expanding lacunae causing triventricular hydrocephalus

Abstract: Two patients are reported in whom the presence of triventricular hydrocephalus and aqueductal obstruction or stenosis due to multiple expanding lacunae in the mesencephalothalamic region possibly corresponds to abnormally dilated perivascular spaces. Placement of a ventriculoperitoneal cerebrospinal fluid (CSF) shunt in one patient and the performance of a third ventricle cisternotomy in the other reversed the hydrocephalic syndrome, but did not modify the complex neuroophthalmological disturbance and rubral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 16 publications
0
31
0
1
Order By: Relevance
“…In some pathological conditions, such as Binswanger’s subcortical arteriosclerotic encephalopathy or ‘expanding lacunae’, the neuropathological demonstration of arteriosclerotic modifications or necrotizing arteritis suggests that alterations of arterial wall permeability may produce the enlargement of VRSs [30]. The term ‘expanding lacunae’ refers to VRSs that may abnormally dilate producing obstructive hydrocephalus [31], dementia [32], temporal lobe epilepsy [33]or even no symptom [34]. Some authors pointed to a possible disorder of brain lymphatic drainage for explaining the expanding character of some VRSs [35].…”
Section: Discussionmentioning
confidence: 99%
“…In some pathological conditions, such as Binswanger’s subcortical arteriosclerotic encephalopathy or ‘expanding lacunae’, the neuropathological demonstration of arteriosclerotic modifications or necrotizing arteritis suggests that alterations of arterial wall permeability may produce the enlargement of VRSs [30]. The term ‘expanding lacunae’ refers to VRSs that may abnormally dilate producing obstructive hydrocephalus [31], dementia [32], temporal lobe epilepsy [33]or even no symptom [34]. Some authors pointed to a possible disorder of brain lymphatic drainage for explaining the expanding character of some VRSs [35].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that they may be the result of altered blood vessel wall permeability due to a vasculitis or lymphatic vessel obstruction [10][11][12]. In several cases, such cystic lesions have been reported in association with aqueduct stenosis [7,8]. We believe that the lesions seen in our case represent dilated Virchow-Robin spaces because of the distribution and signal intensity.…”
Section: Discussionmentioning
confidence: 54%
“…They are usually characterized by an insidious progressive onset of extrapyramidal, hydrocephalic and midbrain syndromes [1,4,5,7]. They can also be asymptomatic [2], presenting as an incidental autopsy finding.…”
Section: Discussionmentioning
confidence: 99%
“…The slight concomitant limb ataxia is attributed to a disturbance of the restiform body or afferent spinocerebellar tract. This clinical condition can occur if the posterior spinal artery or an artery of the posterior group of medullary arteries, all branches of the posterior inferior cerebellar artery, are affected [6][7][8]. With increasing use of MRI the identification of the location and extension of small ischemic lesions is possible, allowing a clear-cut correlation between clinical and anatomical findings ( fig.…”
Section: Dorsal Medullary Infarctionmentioning
confidence: 99%
See 1 more Smart Citation